Araucaria Angustifolia: A Potential Nutraceutical with Antioxidant and Antimutagenic Activities - Michelon, Fabiane; S. Branco, Catia; Calloni, Caroline; Giazzon, Ivana; Agostini, Fabiana; K.W. Spada, Patricia; Salvador, Mirian (Current Nutrition & Food Science, 2012)
The Araucaria angustifolia (Bertolini, Otto Kuntze) tree belongs to the family Araucariaceae and is known as Brazilian pine. The female strobilus consists of seeds (the edible part of A. angustifolia) and bracts (non-developed seeds). These bracts, which represent approximately 80% of the female strobilus, have no use. It has previously been suggested that the dietary intake of antioxidants could be a useful strategy to reduce the incidence of diseases associated with oxidative stress, such as cancer, atherosclerosis and neurodegenerative disorders. This study aimed to evaluate the phenolic profile and the possible antioxidant, mutagenic and antimutagenic activities of the aqueous extract from bracts of A. angustifolia. The results showed that the extract of A. angustifolia presents important in vitro and in vivo antioxidant activity. Additionally, lower concentrations of the extract were non-mutagenic and avoided DNA damage induced by hydrogen peroxide in yeast cells. Catechin, epicatechin and rutin were the main phenolic compounds found in the extract. These results may provide new perspectives for the development of strategies with natural compounds in the nutraceutical field. In addition, the use of this waste will help maintain the environmental balance.
Keywords: Antimutagenic